Importance of Ritu-Charya in Healthy Living with special reference to Basanta Ritu- Charya - Nagar, Lalit Kumar; Sharma, Ashok Kumar; Sharma, Kishori Lal (International Research Journal of Ayurveda & Yoga, 2023)
As environmental properties change with the season, it influences our Tridosha constitution. Ayurveda described 6 Ritu(season) and described ritu charya(seasonal regimen) for living a healthy lifestyle which is necessary for a healthy life. The foremost principle of Ayurveda tantra is to keep individuals healthy, this is an important aspect of preventive medicine in Ayurveda texts. Tridosha gets their different stages(gati) according to Ritu(season); sanchaya(accumulation), prakopa(elevation) and prashamna(alleviation). So particular ritu causes a particular effect on the dosha state, so when someone follows a single diet and lifestyle regimen the whole year this may cause health issues because lifestyle disorders are very common in the modern era and which are originating from ignoring seasonal regimens and following the same or opposite ahara-vihara. This causes Tridosha imbalance and normal physiology changes into pathology as lifestyle disorders. In this article, various diet and lifestyle modifications and regimens as per ayurvedic texts, as well as their importance on lifestyle disorders are described.